2009
DOI: 10.3109/08923970903200716
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of probiotic bacteria,Lactobacillus caseiandBifidobacterium breve, does not exacerbate neurological symptoms in experimental autoimmune encephalomyelitis

Abstract: To evaluate the safety of two probiotic bacterial strains, Lactobacillus casei strain Shirota (LcS) and Bifidobacterium breve strain Yakult (BbY), these probiotics were orally administered to Lewis rats with experimental autoimmune encephalomyelitis (EAE), the experimental model of human multiple sclerosis. We examined three experimental designs by combining different antigen types and probiotic administration periods: (1) EAE was induced with a homogenate of guinea pig spinal cord as the sensitizing antigen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…Differences in neurological symptoms between the control group and the administration groups did not reach statistical significance in experiments 2 and 3. As a result, these findings support the notion that neither LcS nor BbY exacerbates AD [56].…”
Section: Iiia-probiotic Effect In Animal Eae Modelssupporting
confidence: 80%
“…Differences in neurological symptoms between the control group and the administration groups did not reach statistical significance in experiments 2 and 3. As a result, these findings support the notion that neither LcS nor BbY exacerbates AD [56].…”
Section: Iiia-probiotic Effect In Animal Eae Modelssupporting
confidence: 80%
“…Further study is needed to address whether this is also the case for LpYU. Although there are concerns that constitutive Th1 activation results in autoimmune diseases, previous reports revealed that oral administration of probiotic LAB did not induce the pathological inflammation in murine models [49,50]. Therefore, besides activation of Th1 immune responses, probiotic LAB might induce the other regulatory responses.…”
Section: Discussionmentioning
confidence: 90%
“…This has been corroborated by other studies using probiotic mixtures of strains under the Lactobacillus genus. Indeed, Lactobacilli (including LcS), either administrated alone or in combination with other strains of Bifidobacterium genus, tend to alleviate murine EAE symptoms via reciprocal regulation of pro- and anti-inflammatory cytokine responses(Kobayashi et al, 2010; Kobayashi et al, 2012; Kwon et al, 2013; Lavasani et al, 2010). Probiotic treatment with B. fragilis and Pediococcus acidilactici (strain R037) also significantly reduced mice susceptibility to EAE(Ochoa-Reparaz et al, 2010a; Takata et al, 2011).…”
Section: The Role Of Microbiome In Cns Disordersmentioning
confidence: 99%